Transcriptome and Small RNA Sequencing Reveal the Mechanisms Regulating Harvest Index in Brassica napus - Zhang, Chao; Chang, Wei; Li, Xiaodong; Yang, Bo; Zhang, Liyuan; Xiao, Zhongchun; Li, Jiana; Lu, Kun (Frontiers in Plant Science, 2022)
Harvest index (HI), the ratio of harvested seed weight to total aboveground biomass weight, is an economically critical value reflecting the convergence of complex agronomic traits. HI values in rapeseed (Brassica napus) remain much lower than in other major crops, and the underlying regulatory network is largely unknown. In this study, we performed mRNA and small RNA sequencing to reveal the mechanisms shaping HI in B. napus during the seed-filling stage. A total of 8,410 differentially expressed genes (DEGs) between high-HI and low-HI accessions in four tissues (silique pericarp, seed, leaves, and stem) were identified. Combining with co-expression network, 72 gene modules were identified, and a key gene BnaSTY46 was found to participate in retarded establishment of photosynthetic capacity to influence HI. Further research found that the genes involved in circadian rhythms and response to stimulus may play important roles in HI and that their transcript levels were modulated by differentially expressed microRNAs (DEMs), and we identified 903 microRNAs (miRNAs), including 46 known miRNAs and 857 novel miRNAs. Furthermore, transporter activity-related genes were critical to enhancing HI in good cultivation environments. Of 903 miRNAs, we found that the bna-miR396–Bna.A06SRp34a/Bna.A01EMB3119 pair may control the seed development and the accumulation of storage compounds, thus contributing to higher HI. Our findings uncovered the underlying complex regulatory network behind HI and offer potential approaches to rapeseed improvement.